ANALYSIS OF NEW OBSTACLES IN THE AVIATION OPERATION SAFETY AREA AT ISKANDAR PANGKALAN BUN AIRPORT, CENTRAL KALIMANTAN PROVINCE - Labibah, Aulia Nur; Fatimah, Siti; Suryono, Wiwid (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Research on the Flight Operations Safety Area (KKOP) at Iskandar Pangkalan Bun Airport was carried out in 2011. So that in 2024 research related to this matter will be carried out again to analyze and map objects that are suspected to be new obstacles. Based on the discussions that have been carried out, the objects to be studied are as many as 12 points.This research is carried out by tracking directly to each point of the object suspected of being a new obstacle which then the results of the observation will be analyzed for location and height according to its location in the airport KKOP. The result of this study is that it was confirmed that there are 10 out of 12 new obstacle object points at this Airport KKOP which is it will be mapped in the form of an obstacle chart on the Google Earth Pro application.